LISTENING AND SPEAKING SKILLS IN “ENGLISH IN MIND” TEXTBOOK BASED ON THE 2013 CURRICULUM - Hafizah Rifiyanti; Gustaman Saragih (INFERENCE: Journal of English Language Teaching, 2018)
The purpose of this research is to evaluate the compatibility of listening and speaking materials in the textbook “English in Mind” starter level based on the 2013 curriculum that is used in the Indonesian Junior High School for grade VII. This research is designed as a desciptive-evaluative content analysis. The data were collecting by analyzing the content of the textbook particulary listening and speaking parts, consisting of 15 (fifteen) unit including Welcome Unit with 6 sections in each unit. Analysis of the textbook was undertaken on listening and speaking skills, core and basic competencies of the 2013 Curriculum criteria. 1). The result shows that the “English in mind” covers 75% of the criteria of the curriculum listening skill material compatible with the core and basic competence of the 2013 curriculum. The rest 25% of the book content has no compatibility and similarity elements of core and basic competence of the 2013 curriculum. Meanwhile, the textbook “English in Mind”  has fulfilled  100% of the core  and basic competence of the 2013 curriculum for speaking skill material. Key Words: Listening skill, speaking skill, core competencies, basic competencies, The 2013 Curriculum.